The Influence of Implementation of Traditional Games in PJOK Learning on the Social Behavior of Class IV Students at SDS Muhammadiyah 4 Jakarta - Haris, Abdurrahman; Hasani, Ihsan; Sudjana, Eggi (S&Co Publishing, 2024)
This research aims to influence the implementation of traditional games in PJOK Learning on Social Behavior of Class IV Students at SDS Muhammadiyah 4 Jakarta. This type of research is a one group pretest-posttest design. with random sampling technique. The instrument used was a questionnaire which was distributed using a Google form. Data analysis uses descriptive percentages. From the results of the study there were results from social behavior in elementary school students. The conclusion of this study was based on the results of management and analysis of research data on